Global Indian Diasporas Exploring Trajectories of Migration and Theory - Oonk, Gijsbert (IIAS Publications Series, 2007)
This book discusses the relation of South Asian migrants to their homeland, the reproduction of Indian culture abroad and the role of the Indian state in reconnecting migrants of India, focusing on the limits of the diaspora concept, rather than on its possibilities. From a comparative perspective, using examples from South Asian communities in Suriname, Mauritius, East Africa, the UK, Canada and the Netherlands, this collection presents new and controversial insights into the concept of diaspora, raising the question about the limits of its effectiveness as an intellectual concept.